Correlated evolution of LTR retrotransposons and genome size in the genus Eleocharis - Zedek, František; Smerda, Jakub; Smarda, Petr; Bureš, Petr (BMC plant biology, 2010)
BACKGROUND: Transposable elements (TEs) are considered to be an important source of genome size variation and genetic and phenotypic plasticity in eukaryotes. Most of our knowledge about TEs comes from large genomic projects and studies focused on model organisms. However, TE dynamics among related taxa from natural populations and the role of TEs at the species or supra-species level, where genome size and karyotype evolution are modulated in concert with polyploidy and chromosomal rearrangements, remain poorly understood. We focused on the holokinetic genus Eleocharis (Cyperaceae), which displays large variation in genome size and the occurrence of polyploidy and agmatoploidy/symploidy. We analyzed and quantified the long terminal repeat (LTR) retrotransposons Ty1-copia and Ty3-gypsy in relation to changes in both genome size and karyotype in Eleocharis. We also examined how this relationship is reflected in the phylogeny of Eleocharis. RESULTS: Using flow cytometry, we measured the genome sizes of members of the genus Eleocharis (Cyperaceae). We found positive correlation between the independent phylogenetic contrasts of genome size and chromosome number in Eleocharis. We analyzed PCR-amplified sequences of various reverse transcriptases of the LTR retrotransposons Ty1-copia and Ty3-gypsy (762 sequences in total). Using real-time PCR and dot blot approaches, we quantified the densities of Ty1-copia and Ty3-gypsy within the genomes of the analyzed species. We detected an increasing density of Ty1-copia elements in evolutionarily younger Eleocharis species and found a positive correlation between Ty1-copia densities and C/n-values (an alternative measure of monoploid genome size) in the genus phylogeny. In addition, our analysis of Ty1-copia sequences identified a novel retrotransposon family named Helos1, which is responsible for the increasing density of Ty1-copia. The transition:transversion ratio of Helos1 sequences suggests that Helos1 recently transposed in later-diverging Eleocharis species. CONCLUSIONS: Using several different approaches, we were able to distinguish between the roles of LTR retrotransposons, polyploidy and agmatoploidy/symploidy in shaping Eleocharis genomes and karyotypes. Our results confirm the occurrence of both polyploidy and agmatoploidy/symploidy in Eleocharis. Additionally, we introduce a new player in the process of genome evolution in holokinetic plants: LTR retrotransposons.
Keywords: molekulární evoluce; Molecular Sequence Data; Polyploidy; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; sekvence aminokyselin; Genome, Plant; genom rostlinný; Retroelements; Chromosomes, Plant; retroelementy; Terminal Repeat Sequences; DNA, Plant; Base Sequence; sekvence nukleotidů; koncové repetice; Amino Acid Sequence; fylogeneze; DNA rostlinná; Eleocharis; Species Specificity; sekvenční analýza DNA; chromozomy rostlin; sekvenční homologie nukleových kyselin; druhová specificita; molekulární sekvence - údaje; sekvenční homologie aminokyselin; Phylogeny; polyploidie; Sequence Homology, Amino Acid; Evolution, Molecular